Pentingnya Memahami Mitigasi dalam Bencana Banjir, Penyebab Banjir dan Dampak Banjir di Kelurahan Tabing Banda Gadang Kota Padang - Ismayani, Nina; Thesiwati, Aslan Sari; Febrianto, Hary; Putri, Desi Eka (Neolectura, 2024)
The community service activity (PKM) carried out in Tabing Banda Gadang Village, Padang City aims to increase community understanding of the importance of flood disaster mitigation, including its causes and impacts in the area. This activity is designed to provide relevant counselling and training, so that the community has basic knowledge about flood management. In addition, the programme also aims to make the community aware of mitigation measures that can be taken to minimise the risk and impact of floods. The results of this PKM activity show several important things, namely: (1) the community of Tabing Banda Gadang Village gained basic knowledge about flood disaster mitigation, including an understanding of the causes, impacts, and ways to handle flood disasters in their area; (2) the counselling provided succeeded in increasing community awareness and insight into the importance of flood disaster mitigation to deal with the possibility of similar events in the future. This programme provided significant benefits for the community in understanding and preparing for floods.